Dos saberes teóricos aos saberes da ação: a construção de concepções e práticas alfabetizadoras - Ercileia Batista do Espirito Santo (2010)
This research aims to analyze the process of mobilization and appropriation of theoretical knowledge by the literacy educator in its classroom practice. In addition, it is necessary to know, more specifically, which knowledge these educators use to guide their pedagogical practices; identify the origins and possible limitations of their knowledge; analyze the conceptions of literacy underlying learning materials used and the interactions with students; the education trajectories of these professionals; to analyze the process of in-service training; examine the role of the teacher-trainer concerning their strategies for listening and monitoring of the pedagogical work; reflect on research in education as an opportunity for exchange of knowledge between researcher and researched. The main theoretical frame is based on Tardif, Perrenoud, Liston and Zeichner, Shön, in order to analyze the issues concerning teacher knowledge and training. In order to analyze issues related to teacher knowledge and literacy Anne-Marie Chartier, Soares, Piaget, Ferreiro, Teberosky, and Silva, among others were researched. The methodology was based on the principles of collaborative research in accordance with Ibiapinas view (2008). This work was done based on observations, informal conversations, interviews, recordings and notes recorded in a field diary as some of the main instruments of data collection. The results point to the understanding that teachers need help to rebuild concepts and practices of literacy. The learning of theoretical concepts without the chance of doing is not enough to establish the relation between what is learned in college and what is actually done in the classroom. Gaps in literacy teacher training were found and it was detected that it is possible to overcome these problems in training when the gap between theoretical and practical knowledge is reduced. This research revealed the importance of collaborative work between researchers and teachers to guide the teachers to design and reflect on their own practice in an autonomous way. In addition, teachers have to be able not only to understand the theories of literacy but also to relate them to actions in a continuous process of reflection during and about their action, so they can be guided by knowledge and solid foundation.